Sepsis caused by emphysematous pyelonephritis: A case report - Yang, Zheng; Li, Zhihui (Frontiers in Medicine, 2023)
Rationale: Emphysematous pyelonephritis (EPN) is a rare, life-threatening necrotizing renal parenchymal infection and is most commonly seen in patients with poor glycemic control. Patient concerns: We reported a case of a 64-year-old woman presented to the emergency room with fever and weakness over the last 1 days. Diagnosis: After a series of diagnostic workup, the emphysematous pyelonephritis was diagnosed and presented with sepsis. Intervention and outcome: She received conservative treatment with meropenem and symptomatic treatment and the symptoms improved significantly. Lessons: EPN can be reliably diagnosed by non-contrast CT abdominal imaging. The infection is most commonly caused by E. coli species and good curative effect can be got with early diagnosis and precise treatment